Improving the Network Life Time Based on Energy Efficient Routing in Ad Hoc Networks - P. Parthiban; G. Sundararaj (International Journal of Informatics and Communication Technology (IJ-ICT), 2017)
The maximization of a networks lifetime is an important part of research in the present scenario. In ad hoc network, the topology of network changes frequently due to the mobility of mobile nodes where the communication is possible without any network infrastructure. Mobile nodes have limited energy resources so that the energy efficient routing should be provided which increases the life time of the network. The existing routing mechanisms do not consider energy of nodes for data transmission. In this paper a novel approach is analyzed to improve the networks lifetime where the data transfer is based on the minimum hop count and residual energy of the mobile nodes. The analysis is carried out by using the network simulator and the simulation results shows that the proposed work provides an energy efficient routing in ad hoc networks.